Maternal-Fetal Evidence Based Guidelines, 3e 2016
DOI: 10.1201/9781315200910-14
|View full text |Cite
|
Sign up to set email alerts
|

13. Pregnancy after liver and other transplantation

Abstract: This book contains information obtained from authentic and highly regarded sources. While all reasonable efforts have been made to publish reliable data and information, neither the author[s] nor the publisher can accept any legal responsibility or liability for any errors or omissions that may be made. The publishers wish to make clear that any views or opinions expressed in this book by individual editors, authors or contributors are personal to them and do not necessarily reflect the views/opinions of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…11,12,18 Other possible barriers to providing and documenting repro- to allow patients to receive clear and consistent information. [22][23][24] Although our study found stark deficiencies in reproductive health counseling documentation among LT recipients, it does have limitations. While this counseling is likely under-performed, lack of documentation from a retrospective chart review also likely underestimates the true prevalence of counseling that may be occurring outside of a tertiary care setting.…”
Section: Discussionmentioning
confidence: 75%
“…11,12,18 Other possible barriers to providing and documenting repro- to allow patients to receive clear and consistent information. [22][23][24] Although our study found stark deficiencies in reproductive health counseling documentation among LT recipients, it does have limitations. While this counseling is likely under-performed, lack of documentation from a retrospective chart review also likely underestimates the true prevalence of counseling that may be occurring outside of a tertiary care setting.…”
Section: Discussionmentioning
confidence: 75%